TEACHERS' READINESS TO IMPLEMENT THE KURIKULUM MERDEKA IN THE NATURAL AND SOCIAL SCIENCE LEARNING - Mutia, Nur Balqis; Admawati, Harsi (UIN Sunan Kalijaga Yogyakarta, 2023)
Teachers make a major contribution to the success of the new curriculum implementation to enhance the quality of education. Many researchers have studied the implementation of Kurikulum Merdeka, but no studies have specifically explored teachers’ readiness in the natural and social science subject in elementary schools. The purpose of this research was to examine elementary school teachers' readiness in the new curriculum implementation. A qualitative research method was used with twelve teachers in 10 elementary schools in the city of Langsa as the participants of the study. The natural & social science teachers were selected by purposive sampling technique. The participants have been having experiences in practicing the Kurikulum Merdeka since 2022. Individual interviews were used to gather data before reducing, presenting, and drawing a conclusion. In addition, questionnaires were delivered and teachers’ documents were analyzed to obtain the data of the readiness for the planning, implementation, and assessment processes. The result of this study showed that the preparation process was adequate while both the implementation and assessment processes had a good category. The findings of this study were discussed based on the basic concept of learning in the perspective of Islam and Islamic learning methods. The Islamic education methods, namely hikmah, mau’idzah, and jidal, have been applied in the implementation step. Suggestions for teachers’ practice and further research will also be offered based on the research findings.